SYNERGISM OF VITAMIN E AND SELENIUM ON OXIDATIVE STRESS DURING TRANSITION PERIOD IN KANKREJ CATTLE - Parmar, VL; Panchsare, HH; Sutaria, Prajwalita; Staria, TV; Sadhu, DB; Prajapati, HB (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
It has been observed that during the transition period cows experience oxidative stress which may contribute to periparturient disorders and may be associated with metabolic diseases. Vitamin E and selenium (Se) play vital role in reduction of oxidative stress and maintain the health of living animals. The concentration of MDA was significantly (P<0.05) lower in Vit.E + Se supplemented group as compared to control group in stage-I, II and III (late pregnancy, recent parturition and early postpartum) during transition period in Kankrej cattle. However, in the treatment group the SOD level was significantly (P<0.05) reduced as compared to control group at stage of recent parturition.